(untitled) (Journal of Information Systems and Technology Management, 2010)
A study was conducted in the aim to identify whether and how knowledge sharing contributes, through instruments and behavioral aspects, to risk management. Initially, as the literature review was carried out, it was identified, on one hand, the main instruments and behavioral aspects that facilitate knowledge sharing and, on the other hand, the different approaches to risk management in software projects. Following that, the relationship between these two themes was established. Then, based on a case study in the software industry, an analysis was carried out and applied to the development teams, aiming at understanding and perceiving what risk management activities are practiced in software projects, the behavioral factors that may favorably influence knowledge sharing on software projects risks and what instruments of knowledge sharing may contribute, at a certain degree, to risk management in projects.